UJI DAYA HAMBAT EKSTRAK DAUN KEMBANG SEPATU (HIBISCUS ROSA-SINENSIS L.) TERHADAP PERTUMBUHAN BAKTERI PROPIONIBACTERIUM ACNES - LOUSE CHINTIA YUSUF; CUT MOURISA (LP2MTBM MAKARIOZ, 2020)
Propionibacterium acnes (P. acnes) is the main organism which generally contributes to the occurrence of acne. Many plantscan be used as traditional medicine, one of which is the hibiscus leaf (Hibiscus rosa-sinensis L.). This study uses anexperimental method. Extraction was carried out by maceration using 70% ethanol. To determine the inhibition of hibiscusleaf extract (Hibiscus rosa-sinensis L.) with a concentration of 40%, 60% and 80% and to determine the most effectiveconcentration on the growth of P. acnes bacteria in vitro. The technique used to measure antibiotic activity is the discdiffusion method. Data was processed using SPSS Kruskal- Wallis test and continued with Mann-Whitney for different tests.The results showed that hibiscus leaf extract (Hibiscus rosa-sinensis L.) at a concentration of 40%, 60%, and 80%, positivecontrol (clindamycin) and negative control (aquadest) obtained result as (p=0,000) whereas (p=0,05) indicates there aresignificant differences of inhibitory effect in each group. The 80% concentration of hibiscus leaf extract is most effective ininhibiting the growth of P. acnes bacteria compared to concentrations of 40% and 60%. Hibiscus leaf extract can inhibit thegrowth of P. acnes bacteria.